Combination laser interstitial thermal therapy plus stereotactic radiotherapy increases time to progression for biopsy-proven recurrent brain metastases. Issue 1 (2nd June 2022) - Grabowski, Matthew M; Srinivasan, Ethan S; Vaios, Eugene J; Sankey, Eric W; Otvos, Balint; Krivosheya, Daria; Scott, Alex; Olufawo, Michael; Ma, Jun; Fomchenko, Elena I; Herndon, James E; Kim, Albert H; et al.
Abstract: Background: Improved survival for patients with brain metastases has been accompanied by a rise in tumor recurrence after stereotactic radiotherapy (SRT). Laser interstitial thermal therapy (LITT) has emerged as an effective treatment for SRT failures as an alternative to open resection or repeat SRT. We aimed to evaluate the efficacy of LITT followed by SRT (LITT+SRT) in recurrent brain metastases. Methods: A multicenter, retrospective study was performed of patients who underwent treatment for biopsy-proven brain metastasis recurrence after SRT at an academic medical center. Patients were stratified by "planned LITT+SRT" versus "LITT alone" versus "repeat SRT alone." Index lesion progression was determined by modified Response Assessment in Neuro-Oncology Brain Metastases (RANO-BM) criteria. Results: Fifty-five patients met inclusion criteria, with a median follow-up of 7.3 months (range: 1.0–30.5), age of 60 years (range: 37–86), Karnofsky Performance Status (KPS) of 80 (range: 60–100), and pre-LITT/biopsy contrast-enhancing volume of 5.7 cc (range: 0.7–19.4). Thirty-eight percent of patients underwent LITT+SRT, 45% LITT alone, and 16% SRT alone. Median time to index lesion progression (29.8, 7.5, and 3.7 months [ P = .022]) was significantly improved with LITT+SRT. When controlling for age in a multivariate analysis, patients treated with LITT+SRT remained significantly less likely to have index lesion progression ( P = .004). Conclusions: These data suggest that LITT+SRT is superior to LITT or repeat SRT alone for treatment of biopsy-proven brain metastasis recurrence after SRT failure. Prospective trials are warranted to validate the efficacy of using combination LITT+SRT for treatment of recurrent brain metastases.